2020
DOI: 10.1002/cc.20421
|View full text |Cite
|
Sign up to set email alerts
|

Exploring How Institutional Partners Vary in Outcomes for Transfer Students of Color

Abstract: Institutional pairs of community college‐sending institutions and university‐receiving institutions are associated with significant variation in college completion outcomes, with such variation being especially pronounced for underserved transfer students of color. Higher performing institutional pairs tend to enroll a predominantly White student body, which highlights how inequities in transfer continue to manifest as a baccalaureate completion gap for transfer students of color.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…At the same time, transfer partnerships do not necessarily produce equitable outcomes. For instance, Meza and Blume (2020) found racial inequities in transfer between 308 institutional pairs in which students of color completed bachelor's degrees at rates comparable to White students. To produce equitable outcomes, transfer partnerships must center equity in the design, implementation, and evaluation of programs.…”
Section: Purpose and Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, transfer partnerships do not necessarily produce equitable outcomes. For instance, Meza and Blume (2020) found racial inequities in transfer between 308 institutional pairs in which students of color completed bachelor's degrees at rates comparable to White students. To produce equitable outcomes, transfer partnerships must center equity in the design, implementation, and evaluation of programs.…”
Section: Purpose and Objectivesmentioning
confidence: 99%
“…Transfer partnerships also exist in multiple forms. For instance, some partnerships emerge from a review of student success data (Meza & Blume, 2020), while others are built from faculty relationships that evolve into partnerships (DeChano-Cook & Casey, 2020). For some institutions, partnerships are created from shared resources and enrollments that allow students to move between institutions as needed (Clemetsen & Balzer, 2008).…”
mentioning
confidence: 99%
“…On average, Black and Hispanic students have many risk factors to begin with: many come from lower‐income families, start at community colleges or less selective institutions, and delay college enrollment at least a year after high school graduation at higher rates than White and Asian students, all of which are negatively related to successful transfer to 4‐year institutions (Crisp et al., 2020). Even when Black and Hispanic students successfully transfer to 4‐year institutions, they are less likely to attempt to transfer credits from community colleges (Crisp et al., 2020) and their odds for bachelor's degree completion are lower than those for white middle‐income students (Meza & Blume, 2020). Considering that Promise scholarships would attract many low‐income racial minority students who aspire to earn a bachelor's degree to start at community colleges, we strongly recommend community colleges identify barriers facing these students through surveys or focus groups, hire chief diversity or equity officers, and provide equity‐oriented supports (Wellington‐Baker & Hammer, 2020).…”
Section: Lessons Learned and Recommendationsmentioning
confidence: 99%
“…Recommendations to improve transfer policy within states and institutions abound (Crowe et al., 2020; Yeh & Wetzstein, 2020); changes in transfer policy and practice are especially crucial for students of color and low‐income students, who research has shown, are disproportionately impacted by barriers to successful transfer (Budd & Stowers, 2015; Dougherty & Kienzl, 2006; La Sota & Zumeta, 2016; Taylor & Jain, 2017). A recent study by Meza and Blume (2020) found evidence of a racial transfer gap and suggests that good transfer policy and practice at receiving institutions is particularly important to addressing to these inequities (Crisp et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Innovation in policy and practice, and collaboration among higher education institutions and between states are required to address the transfer challenge (Crowe et al., 2020; Meza & Blume, 2020; Yeh & Wetzstein, 2020). This article describes the Interstate Passport, a innovative collaborative effort to improve transfer, focusing on its implementation at a rural community college.…”
Section: Introductionmentioning
confidence: 99%